2003
DOI: 10.1046/j.1570-7458.2003.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Trap cropping to control Delia radicum populations in cruciferous crops: first results and future applications

Abstract: This study evaluates the efficacy of a new approach to the control of Delia radicum populations. We suggest associating the primary crop with a trap crop that is expected to be more attractive to D. radicum females and to attract and sustain their natural enemies such as Aleochara bilineata and A. bipustulata. Various cruciferous species were compared in terms of their preference for adult D. radicum females, and performance, as estimated by larval survival. Laboratory results were complemented by field experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Although it is already known to deter oviposition in some insect pests (Furtado et al 2014;Mbata and Payton 2013;Murungi et al 2013), it was also identified as the major compound in the Chinese cabbage VOC blend (Kergunteuil et al 2015) which is very attractive to D. radicum (Rousse et al 2003). Accordingly, we had made the hypothesis that linalool could be used as a 'pull' factor, i.e., we postulated that it would attract D. radicum and induce more damage in linalool-treated plots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is already known to deter oviposition in some insect pests (Furtado et al 2014;Mbata and Payton 2013;Murungi et al 2013), it was also identified as the major compound in the Chinese cabbage VOC blend (Kergunteuil et al 2015) which is very attractive to D. radicum (Rousse et al 2003). Accordingly, we had made the hypothesis that linalool could be used as a 'pull' factor, i.e., we postulated that it would attract D. radicum and induce more damage in linalool-treated plots.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to the necessary 'pull' component, D. radicum host preferences have been compared among cultivated Brassicaceae, and Chinese cabbage (Brassica rapa L. subsp. pekinensis) appears to be highly attractive (Rousse et al 2003), making it a good potential candidate.…”
Section: Introductionmentioning
confidence: 99%
“…When this does not happen, i.e., when the trap crop consists of relatively non-preferred host plants, it results in failure of pest management system (Rust 1977;Maguire 1984). Where trap crops have proved successful in managing insect-pests, they were grown as border rows surrounding the main crop or as strips running at right angle to the pests' entry route into the crop (Srinivasan and Krishna Moorthy 1991;Luther et al 1996;Mitchell et al 2000;Asman 2002;Rousse et al 2003;Barari et al 2005;Fearson et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Using such a trap for auto-dissemination of insect pathogenic fungi that kill D. radicum and D. floralis combined with intercropping may be an interesting component in a pushpull strategy. Studies have shown that Chinese cabbage is more attractive to D. radicum than many other Brassicaceae vegetables (Rousse et al, 2003). Preliminary results further suggest that both healthy D. floralis, and D. floralis infected with the insect pathogenic fungus Enthomophtora muscae, prefer to oviposit on Chinese cabbage than on broccoli (Klingen, unpublished data).…”
Section: 'Push-pull' Systems For Effective Pest Controlmentioning
confidence: 95%